Construction of the Hainan Free Trade Port from the perspective of regional cultural development - Xiu, Chunliang; Li, Tong (Frontiers in Earth Science, 2023)
This study summarizes the internal relationship and mechanism of industrialization, business culture, and higher education that affect the development of modern industrial and commercial culture, and consequently, the construction of free trade ports in Hainan. The cases of Hong Kong, Singapore, and Dubai free trade ports were considered as references. Based on immigration, naturalization, and education in Hainan’s history, Hainan’s cultural base map, which influences the construction of modern industrial and commercial culture, was proposed to be formed by splicing and overlapping of the free, guarding, farming-reading, farming-marine, and immigrant cultures. The development course of Hainan in the past 30 years indicated that although Hainan has always been at the forefront and highland of reform and opening up, it is still relatively backward despite the implementation of long-term policies; moreover, its development performance is not ideal. The existing problems and factors related to the present ideology mainly include the following: (1) The pursuit of “making quick money” has led to the ups and downs of Hainan's development. (2) Lack of innovation hinders functional improvement leading to poor sustainability. (3) The course of modern industrial civilization based on a cultural base map is short. (4) Although bottom-up industrialization plays a key role in the formation of modern industrial civilization, it is not followed by Hainan. Furthermore, the cultural development path of Hainan Free Trade Port construction should (1) strongly promote industrialization by overcoming the shortcomings of industrial development, (2) deepen the reform of the agricultural reclamation system, improve the business environment, and cultivate a healthy modern industrial and commercial culture, (3) standardize the tourism market, and build the most advanced tourism industry culture, (4) improve the basic education level and develop excellent higher education opportunities, (5) enhance the diversity of human resources structure, and (6) revitalize literature and art, and showcase and develop Hainan’s fine culture. Overall, the construction of the Hainan Free Trade Port requires long-term upgrading and development. It is necessary to continue cultural construction, adapt to the requirements of the highest level of openness and realize the healthy development of the Hainan Free Trade Port.